Kekuatan Penokohan dan Nilai Pendidikan dalam Novel Bidadari-Bidadari Surga Karya Tere Liye: Sebuah Analisis Pendekatan Struktural - Nilawijaya, Rita; Awalludin, Awalludin; Monalisa, Egi (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
This study aims to describe the characters and characterizations contained in the novel Bidadari-Bidadari Surga by Tere Liye and to describe the educational values ​​contained in the novel Bidadari-Bidadari Surga by Tere Liye. The method used in this study is a descriptive method using a structural approach. The data collection technique used is the documentation technique. Furthermore, the data analysis technique used in this study is a novel document content analysis technique. The results of this study indicate that the characters who play a role and build the story in the novel Bidadari-Bidadari Surga by Tere Liye are Laisa, Mak Lainuri, Dalimunte, Ikanuri, Wibisana, and Yashinta. Furthermore, the characterizations painted on these characters are: Laisa has a hard-working and firm character, Mak Lainuri has a gentle and kind character, Dalimunte is a smart and obedient character, Ikanuri is described as a naughty but kind character, Wibisana is a character who is a little naughty but in principle he is a good person, and Yashinta is a beautiful story character and has a good personality. In addition to the strength of the characters and characterizations, educational values ​​are also the strengths that are presented in the novel, namely religious, honesty, tolerance, discipline, hard work, creative, independent, democratic values, respect for achievement, communicative, peace-loving, reading, caring for the environment, social care, and responsibility. For this reason, Tere Liye's novel Bidadari-Bidadari Surga is suitable as reading material and as teaching material for the basic competence of writing novels in schools.